The chemopreventive effects of Nigella sativa extract and Thymoquinone in a paternal toxicity study - Abdul Samat, Nadia Hanis; Abdul Rahman, Suzanah; Ahmad, Nur Amalina (2015)
Studies have reported that exposure to cyclophosphamide (CPA) for cancer treatment result in adverse reproductive consequences. Over-production of reactive oxygen species causes oxidative stress thus affecting the DNA in male germ cell thus induces sperm defects. Our goal is to assess the potential effect of Nigella sativa extract (NSE) and thymoquinone (TQ) on sperm and embryo quality following fertlization from sperm produced from germ cells which have been exposed to the damaging alkylating effects of CPA. Thirty Balb/c mice were divided into six groups; (i) Control, (ii) NSE only, (iii) TQ only, (iv) CPA only, (v) CPA with NSE and (vi) CPA with TQ. Treatment was given to the mice based on the grouping for 32 days where the dosage for CPA is 200mg/kg and for NSE and TQ 10mg/kg. Groups (v) and (vi) were treated with CPA followed by NSE and TQ after six hours. Animals were sacrificed at 33rd days by cervical dislocation and sperm from testis and epidydymis were taken for in vitro fertilization (IVF) with eggs from untreated female and sperm analysis. Fertilization rates and embryo development were assessed and monitored for 5 days. TQ and NSE supplementation to CPA-exposed male mice have no significant effect (p>0.05) on the total number of sperm when compared to non treated CPA-exposed mice (p value = 0.498). NSE supplementation has been shown to have significant effect (p<0.05) on the percentage of double stranded DNA in the sperm head (p value = 0.034). The result shows an increment in fertilization rate in IVF if the CPA exposure is followed by the treatment with NSE (p value = 0.014, p<0.05). Finally, the embryo quality based on embryo scoring by Baczkowski (2004), was not affected by the supplementation of TQ and NSE to CPA-exposed male mice (p value = 0.235). Overall, both NSE and TQ have the chemoprotective potential against the cytotoxicity of cyclophosphamide on the reproductive capacity and fertility in the animal model.